Soy-Dawadawa Production by Traditional Spontaneous Fermentation inside Pieces of Jute Sack - O.O., Efunwoye; O.R., Oluwole; V.O., Alagbe; K.S., Olawale; O.O., Ajibola; B.I., Omotoyinbo (International Journal of Scientific Research in Biological Sciences, 2021)
Soybean is a highly nutritious legume that is easy to cultivate and process, which can provide a suitable substitute for African locust bean in the production of dawadawa, a widely consumed condiment in the West African region. Traditional spontaneous fermentation of soy-dawadawa using jute sack was carried out to study the effect on the microorganisms implicated and the activities of enzymes involved in the process. The total microbial count of the microorganisms involved in the fermentation increased with fermentation time (72 hr). The only microorganism isolated was Bacillus subtilis, without identifying any lactic acid bacteria nor fungi. The pH of the fermenting soybean rose from 6.60 to 8.04, in an alkaline fermentation process. Moisture content in the fermenting bean exhibited significant increase until 48 hr of fermentation, after which it declined. The crude fibre content displayed an irregular pattern over the fermentation period. Crude protein in the soy-dawadawa significantly increased with fermentation time, which increased digestibility of the soybean. The ash content showed no regular pattern across fermentation period, while the crude lipids content reduced significantly with fermentation period. The carbohydrates content showed no significant change from 0 hr to 24 hr but increased significantly at that point to the end of fermentation. Protease activity increased from 0.006297 mg/ml/min (0 hr) to 0.013524 mg/ml/min (72 hr) to explain the observed increase in the protein content. Lipase activity rose from initial 0.262674 mg/ml/min and ended at 1.759916 mg/ml/min which shows direct relation to the reduction in the crude lipid content. Trypsin inhibitors in the soybean dropped with fermentation time with the values at 32.31 % (0 hr) and 11.58 % (72 hr). Fermentation time had influence on the fermentation parameters. Fermentation of soy-dawadawa in jute sack led to an improvement in the overall nutrition and digestibility of the soybean.